2013
DOI: 10.4028/www.scientific.net/amm.353-356.1970
|View full text |Cite
|
Sign up to set email alerts
|

Study on Similarity of Hysteretic Loops and Characteristic Parameters of Viscoelastic Dampers with Test Verifications

Abstract: There are similarity relations in hysteretic loops and parameters of viscoelastic (VE) dampers with same material but various sizes. Similarity coefficients of damper force and deformation of hysteretic loops were derived, and then similarity coefficients of characteristic parameters of VE dampers with various sizes were obtained consequently. Based on the similarity criteria, if the hysteretic loops of one of a series of VE dampers with same material but various sizes are obtained through test, then hystereti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Larger displacement and force capacity dampers are needed to control dynamic response of buildings especially under seismic loadings. Moreover, it was shown that the VE dampers with various sizes exhibit significantly different mechanical properties even though they employ the same elastomeric material . Therefore, while studying vibration control of civil structures with VE damper, the size effects should be taken into account on the basis of related experimental tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger displacement and force capacity dampers are needed to control dynamic response of buildings especially under seismic loadings. Moreover, it was shown that the VE dampers with various sizes exhibit significantly different mechanical properties even though they employ the same elastomeric material . Therefore, while studying vibration control of civil structures with VE damper, the size effects should be taken into account on the basis of related experimental tests.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have been conducted experimentally characterize mechanical response of VE dampers under different loading conditions. However, most of these studies have been on small capacity dampers, which had a rubber thickness of 5, 10, or between 12 and 15 mm and a shear area of less than 15,000 mm 2 . Larger displacement and force capacity dampers are needed to control dynamic response of buildings especially under seismic loadings.…”
Section: Introductionmentioning
confidence: 99%
“…Se cuantifica también la notable mejora en el comportamiento sísmico debida a la introducción de los disipadores histeréticos. (Nielsen, Mualla, & Iwai, 2004), c) viscoelastic solid (Zhou, Gong, & Lu, 2013)…”
Section: Introductionunclassified